Synthesis of Some Nitrosubstituted Flavanones, Pyrazolines and Their Derivatives - PARMAR, P.J.; RAJPUT, S.I.; DOSHI, A.G. (Asian Journal of Chemistry, 2010)
2-Hydroxy-3-nitro-5-methyl acetophenone (Ia) condenses with 3,4-substituted benzaldehyde (IIa-d) in ethanol medium in presence of aqueous NaOH to give chalcones (IIIa-d). Chalcones (IIIa-d) refluxed with 80% ethanol and concentrated sulphuric acid to give flavanones (IVa-d). Chalcones (IIIa-d) reacted with hydrazine hydrate in ethanol to give pyrazolines (Va-d). Chalcones (IIIa-d) or flavanones (IVa-d) refluxed with hydrazine hydrate, piperidine and ethanol to give same pyrazolines (Va-d). Pyrazolines (Va-b) reacted with acetic acid to form 1-acetyl pyrazolines (VIa-b). Pyrazolines (Va-b) or 1-acetyl pyrazolines (VIa-b) reacted with acetic anhydride and a pinch of anhydrous sodium acetate to give 1-acetyl-2-acetoxy pyrazolines (VIIa-b). Pyrazolines (Va-b) were condensed with benzoyl chloride in pyridine medium to give 1-benzoyl pyrazolines (VIIIa-b). The structures of all compounds were established on the basis of spectral data (UV, IR, PMR), elemental analysis and chemical properties.